Synthesis of Some Imines and Investigation of their Biological Activity - Majed M. Hania (E-Journal of Chemistry)
Some N-benzylidene aniline derivatives have been synthesized and tested as antibacterial agents. The results of the in vitro tests showed that most of the synthesized compounds were antibacterial inactive against E.coli.